Splintage in the treatment of sagittal band incompetence and extensor tendon subluxation. (March 2015) - Peelman, J.; Markiewitz, A.; Kiefhaber, T.; Stern, P.
This study assessed the success of splintage for traumatic and atraumatic sagittal band incompetence and its relationship to the duration of symptoms before treatment. A retrospective review of all patients with sagittal band incompetence treated with splintage was performed. All patients had extensor tendon subluxation on physical examination. Ninety-two patients were included: 68 traumatic and 24 atraumatic. Subluxation resolved with splintage in 77 patients. Traumatic tendon subluxation resolved in 95% of acute injuries, 100% of subacute injuries, and 67% of chronic injures. Atraumatic tendon subluxation resolved in 100% of patients with acute presentation, 67% of patients with subacute presentation, and 57% of patients with chronic presentation. Surgery was rarely required. Splintage proved very effective for acute sagittal band incompetence, regardless of causation, but decreased in efficiency with chronicity. Level of evidence: Level 4